The effect of viscosity on particle suspension in an aerated stirred vessel with different impellers and bases - Ibrahim, Shaliza; Nienow, A.W. (Taylor & Francis, 2010)
The agitator speed required to suspend solids under gassed conditions, N JSg, has been studied in water and in corn syrup of 0.01 and 0.1 Pas giving Reynolds numbers from the full turbulent region down to ~10 3. Of the impellers tested, the downpumping, three-blade, axial flow hydrofoil impellers are generally unsuitable for this duty, and although six-blade, mixed flow down-pumping impellers require the lowest mean specific energy dissipation rates to suspend the solids, (T) JSg, at low gas flow rates, they are still prone to flow instabilities and torque fluctuations. The latter poor characteristics are made worse by reducing the size of the impeller relative to the vessel and by increasing viscosity and gas flow rate, QGV. Thus, they are of limited use for such systems. The Ekato InterMIG impeller has the highest (T) JSg and tends to cause vessel vibrations when dispersing the gas, and this weakness is also enhanced by increasing viscosity and gas flow rate. Again, they are generally not appropriate for three-phase systems. The radial flow Rushton turbine is quite stable and able to suspend the solids in all the fluids. However, it requires the second highest (T) JSg, and both (T) JSg and NJSg increase substantially with increasing QGV. The up-pumping six-blade, mixed flow impeller of approximately half the vessel diameter is able to suspend the solids and is very stable in all the fluids. In addition, both (T) JSg and NJSg are very insensitive toQGV, with (T) JSg generally being the lowest at the highest QGV. It is thus the preferred agitator among those tested. As in ungassed systems, modifying the base of the vessel can significantly lower (T) JSg and NJSg for a given impeller type in water compared to a flat base. The concept of keeping constant torque as a means of maintaining suspension has been tested and found not to be valid in this work. Another approach to generalizing the results is also suggested. Â© Taylor & Francis Group, LLC.